2023
DOI: 10.26434/chemrxiv-2023-wgv41
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spiroindoles as Intermediates/Products in Transition Metal Catalyzed Dearomatization of Indoles

Abstract: Spirocyclic indole derivatives are fascinating tridimensional molecular scaffolds, from both a synthetic and biological point of view. Among the diversity of strategies developed to access this kind of structures, transition metal catalysis recently led to impressive advances, especially in order to tame the unique reactivity of the dearomatized spirocyclic intermediates. These species can indeed evolve towards both spirocyclic or non-spirocyclic products through rearomatization-driven processes which are at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Subsequently, further investigation study of the effect of solvents for this reaction indicated that CH 2 Cl 2 was the most suitable solvent to deliver product 3a in 95% yield (in Table 1, entry 4). None of them (such as CHCl 3 , DCE, THF, dioxane, Et 2 O, EtOAc, CH 3 CN, and toluene) showcased better effectiveness than CH 2 Cl 2 in this reaction (in Table 1, entries [5][6][7][8][9][10][11]. Decreasing the catalyst loading to 10 mol% led to a lower yield (83% yield) even if further prolonging reaction time (in Table 1, entry 12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, further investigation study of the effect of solvents for this reaction indicated that CH 2 Cl 2 was the most suitable solvent to deliver product 3a in 95% yield (in Table 1, entry 4). None of them (such as CHCl 3 , DCE, THF, dioxane, Et 2 O, EtOAc, CH 3 CN, and toluene) showcased better effectiveness than CH 2 Cl 2 in this reaction (in Table 1, entries [5][6][7][8][9][10][11]. Decreasing the catalyst loading to 10 mol% led to a lower yield (83% yield) even if further prolonging reaction time (in Table 1, entry 12).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its importance in fields like chemistry, biology, and medicine, the preparation of substituted indole derivatives has increasingly gained significant attention over the years, and numerous effective and advanced methodologies have been well developed [6][7][8][9]. Especially, dearomatization reactions of indole heterocycle represent a novel and powerful approach for assembling high value-added three-dimensional polycyclic molecules with multiple stereocenters in a single step [10][11][12][13][14][15][16][17][18]. On the other hand, tetrahydroquinoline skeletons, as a potent pharmacophore exhibiting significant biological activities, are frequently found in many bioactive natural products and synthetic compounds [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Because of their high importance in both synthetic and pharmaceutical chemistry, tremendous efforts have been devoted to the development of synthetic strategies for accessing structurally diverse spiroindolenines. 2 One of the most efficient approaches for constructing spiroindolenines involves dearomatization of indoles via intramolecular nucleophilic addition of indole C3 to a tethered electrophilic moiety (Scheme 1A). 3 Despite significant advances in this area, most of the reported methods have focused on the construction of spiroindolenines featuring an indolenine unit spiro connected to a five-or six-membered ring; seven-membered ring-containing spiroindolenines have rarely been reported.…”
mentioning
confidence: 99%
“…S piroindolenines are encountered as substructures in bioactive alkaloid natural products and serve as precursors for the construction of other privileged heterocycles such as indolines, oxindoles, and 2,3-disubstituted indoles. 1,2 Because of their high importance in both synthetic and pharmaceutical chemistry, tremendous efforts have been devoted to the development of synthetic strategies for accessing structurally diverse spiroindolenines. 2 One of the most efficient approaches for constructing spiroindolenines involves dearomatization of indoles via intramolecular nucleophilic addition of indole C3 to a tethered electrophilic moiety (Scheme 1A).…”
mentioning
confidence: 99%
“…Various methodologies have been documented for the synthesis of spiroindolines, which feature a spirocyclic stereocenter positioned at the C3 position. 1 The investigation of isomeric C2 spiroindoline derivatives (including spirooxindoles) has been limited comparatively. 2,3 However, C2-spiropseudoindoxyl is commonly found in natural products (Scheme 1a).…”
mentioning
confidence: 99%